Աքսորյալ զեյթունցիների զինված դիմադրության փորձը Դեր Զորի անապատում - Թաթոյան, Ռոբերտ Ա. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The article covers the history of an exceptional episode of self-defense of Armenians during the second stage of the Armenian Genocide, the armed resistance of Armenians from Zeitun in one of the caravans of Armenian exiles driven to the desert after the liquidation of the Der Zor concentration camp in the summer of 1916. The sources of the work are the testimonies of survivors, who witnessed the events, especially the unpublished memoirs of Tigran Makaryan kept in the scientiﬁc funds of the Armenian Genocide Museum-Institute. According to sources: 1. The resistance took place in the first half of August 1916 in the Shedadieh concentration camp. 2. The immediate cause of the resistance was the attempt to recruit men into labor battalions. 3. The resistance lasted for two or three days was cruelly suppressed. 4. The number of Armenian men who directly participated in the resistance was around 100-120, of which about a third had firearms. 5. 200 cavalry gendarmes, as well as auxiliary bands of Arabs and Circassians joined the suppression of resistance. At least 8-10 gendarmes were killed during fight. 6. Der Zor governor Salih Zeki personally directed the suppression of the resistance. В статье освещена история исключительного эпизода самообороны армян во время второго этапа геноцида – вооруженного сопротивления армян Зейтуна в одном из караванов армянских депортированных, согнанных в пустыню после ликвидации концентрационнго лагеря в Дер Зоре летом 1916 года. Источниками работы являются свидетельства выживших, которые были свидетелями событий, в частности неопубликованные воспоминания Тиграна Макаряна, хранящиеся в научных фондах Музея-института Геноцида армян. По данным источников: 1. Сопротивление произошло в первой половине августа 1916 года в концентрационном лагере у Шедадие.2. Непосредственной причиной сопротивления была попытка насильственного рекрутирования мужчин в трудовые батальоны. 3. Сопротивление, продолжавшееся два-три дня, было жестоко подавлено. 4. Число армянских мужчин, непосредственно участвовавших в сопротивлении, составляло около 100-120 человек, из которых около трети имели огнестрельное оружие. 5. К подавлению сопротивления присоединились 200 кавалерийских жандармов, а также вспомогательные банды арабов и черкесов. В ходе боя было убито по меньшей мере 8-10 жандармов. 6. Губернатор Дер Зора Салих Зеки лично руководил подавлением сопротивления.
Keywords: Հայոց ցեղասպանություն